Changes in snowmelt runoff timing in the contiguous United States. Issue 11 (21st November 2021) - Uzun, Sukru; Tanir, Tugkan; Coelho, Gustavo de A.; Souza de Lima, Andre de; Cassalho, Felicio; Ferreira, Celso M.
Abstract: Changes in timing of snowmelt‐fed streamflow have great importance for water supply, flood management, and ecological processes, as well as being a common indicator of climate change. In this study, snowmelt runoff timing change in the contiguous United States between 1957 and 2016 was investigated by analysing data from 97 streamflow gages. The annual snowmelt runoff timing shift was identified using 'Center Time (CT)' and 'Spring Pulse Onset (SPO)' methods, jointly with the monthly fractional streamflow (MFS) analysis, conducted between January and June. Since snowmelt‐derived streamflow timing change is mainly induced by regional meteorological factors, such as air temperature and precipitation, their trends and relationship with CT were also examined. Shifts toward earlier snowmelt runoff timing were found by both methods, CT (8.3 days on average) and SPO (8.5 days on average). Although the results of the CT change are stronger than the SPO change, both outcomes are mostly correlated, particularly in the central and northwestern parts of the country. MFS trends support the outcomes of CT and SPO. In January, February, and especially March, a higher number of the stations indicated increasing trends in MFS. In April, May, and June, their number decreased and the number of gages with diminishing trends rose sharply. The timing difference is highly related to temperature change. Annual average temperature and temperature in the melting period increase considerably. The annual average temperature is significantly negatively correlated with CT in the vast majority of the regions. Although precipitation is not as effective as the temperature, its trends have impacts on snowmelt runoff timing change depending on the region and elevation. These results demonstrate the importance of the impacts of snowmelt runoff timing changes due to global warming on the regional and large‐scale hydrology in the contiguous United States. Abstract : In this study, snowmelt runoff timing change in the contiguous United States between 1957 and 2016 was investigated. Shifts toward earlier snowmelt runoff timing were found by the methods, Center Time (8.3 days on average) and Spring Pulse Onset (8.5 days on average). While the annual average temperature is significantly negatively correlated with snowmelt runoff timing in the vast majority of the regions, precipitation trends have slight impacts on snowmelt runoff timing change depending on the region and elevation.